Guyana : Poverty Reduction Strategy Paper Second Annual Progress Report; Joint Staff Advisory Note. (IMF Staff Country Reports; Country Report ;, 2006)
Guyana continues to make progress in laying the foundation for poverty reduction, but at a slow pace. Critical issues remain to be addressed. Establishing an environment for sustained growth remains the main challenge for the government. It will be important to maintain the reform momentum and ensure basic security. An effective monitoring and evaluation framework needs to be fully implemented to support poverty reduction efforts. Prudent fiscal policies and a prioritized public sector investment program should continue to be pursued to improve debt sustainability prospects.